Enhanced ductility and toughness of desert sand engineered cementitious composites - Wang, Dan; Che, Jialing; Liu, Haifeng; Siew Choo, Chin (MDPI, 2023)
Economical desert sand engineered cementitious composites (DS-ECCs) using a mixture of cement, fly ash, local desert sand, water, low-cost PVA fibers, and chemical additives were developed, aiming for a further enhancement in ductility and toughness. The mechanical behavior of DS-ECCs for two sand samples (from Mu Us and Tengger deserts, China) was determined using uniaxial tension/compression tests and three-/four-point bending tests. The results showed that desert sand-based ECCs with the designed mix ratios had better mechanical properties than the river sand-based ones. Compared with the river sand-based ECCs at 28 and 56 day, the DS-ECCs presented superior ultimate tensile and comparable compression strengths. The excellent ductility was characterized by ultimate tensile and compression strains of 3–7% and over 1%, respectively. Meanwhile, the DS-ECCs showed improved flexural properties with outstanding fracture and bending strengths (4–9 kN and 21–30 kN) and toughness. The findings of this study will further strengthen the mechanical performance of DS-ECCs and broaden their engineering applicability.